2020
DOI: 10.1161/strokeaha.119.028072
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mononuclear Cells Activate Angiogenesis via Gap Junction–Mediated Cell-Cell Interaction

Abstract: Background and Purpose— Bone marrow mononuclear cells (BM-MNCs) are a rich source of hematopoietic stem cells and have been widely used in experimental therapies for patients with ischemic diseases. Activation of angiogenesis is believed to be one of major BM-MNC mode of actions, but the essential mechanism by which BM-MNCs activate angiogenesis have hitherto been elusive. The objective of this study is to reveal the mechanism how BM-MNCs activate angiogenesis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…BCECF-AM was converted to BCECF (2 ,7 -bis-(2-carboxyethyl)-5-(6)-carboxyfluorescein) at cytoplasm, and BCECF-loaded BM-MNCs were washed twice with PBS before injection. 1 × 10 5 BCECF-loaded BM-MNCs in 100 µl PBS was injected to aged mice (80 weeks old, N = 2), and the transfer of BCECF from transplanted BM-MNCs to cerebral endothelium was evaluated by immunohistochemistry as described previously (Kikuchi-Taura et al, 2020). Briefly, at 10 min after cell injection, mice were anesthetized with sodium pentobarbital.…”
Section: In Vivo Transfer Of Low Molecular Weight Fluorescence Molecumentioning
confidence: 99%
See 3 more Smart Citations
“…BCECF-AM was converted to BCECF (2 ,7 -bis-(2-carboxyethyl)-5-(6)-carboxyfluorescein) at cytoplasm, and BCECF-loaded BM-MNCs were washed twice with PBS before injection. 1 × 10 5 BCECF-loaded BM-MNCs in 100 µl PBS was injected to aged mice (80 weeks old, N = 2), and the transfer of BCECF from transplanted BM-MNCs to cerebral endothelium was evaluated by immunohistochemistry as described previously (Kikuchi-Taura et al, 2020). Briefly, at 10 min after cell injection, mice were anesthetized with sodium pentobarbital.…”
Section: In Vivo Transfer Of Low Molecular Weight Fluorescence Molecumentioning
confidence: 99%
“…We had shown that transfer of low molecular weight substance from transplanted BM-MNCs to cerebral endothelial cells is the prominent pathway in the activation of endothelial cells by BM-MNC transplantation after cerebral ischemia (Kikuchi-Taura et al, 2020). To evaluate the transfer of low molecular weight substance from transplanted BM-MNCs to cerebral endothelial cells in aged mice, BCECF-loaded BM-MNCs were injected, and mice were sacrificed at 10 min after injection.…”
Section: In Vivo Transfer Of Low Molecular Weight Substance From Bm-mmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, bone marrow mononuclear cells (BM-MNC) have been shown to activate the repopulation or regeneration of neovascularization in ischemic tissue (Tateishi-Yuyama et al, 2002 ; Taguchi et al, 2003 ). Furthermore, a recent study has demonstrated that transplanted BM-MNCs activate angiogenesis through gap junction-mediated, direct cell-to-cell interactions between BM-MNC and ECs, followed by activation of HIF-1α, and suppression of autophagy in the ECs of ischemic brain tissue (Kikuchi-Taura et al, 2020 ). These studies suggest that stem cell-based therapies, which have utilized MSCs, ASCs, and BM-MNCs, have great potential for neovascularization in neural diseases.…”
Section: Cell Therapy Targeting Of Neovascularization For Neural Disementioning
confidence: 99%